2020
DOI: 10.1002/dc.24592
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of the aptima HPV assay in 4196 women with positive high‐risk HPV and ASC‐US cytology: A large women hospital experience

Abstract: Background Despite Aptima assay as the latest US Food Drug Administration (FDA)‐approved high‐risk human papillomavirus (hrHPV) test has been implemented as an adjunct in cervical cancer screening for years, histological follow‐up data remain limited with respect to its performance in women with ASC‐US Pap tests and positive hrHPV results. Methods Cases with results of ASC‐US cytology and positive hrHPV by Aptima assay during the period 06/ 2015–02/2017 were retrieved from archived pathology reports. Immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Compared with DNA-based HPV tests, the mRNA-based AHPV test shows a similar sensitivity and a higher specificity in high-grade cervical lesion detection 25. Our results showed that the prevalence of HSIL+lesions in women with ASC-US/hrHPV+ based on the Aptima assay are low (12.2%), which is similar to the findings of previous studies (<10%) 17 20 26. However, Jiang et al showed that the prevalence of HSIL+lesions in women with ASC-US/hrHPV+ based on the hrHPV genotype was 19.5% 27.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Compared with DNA-based HPV tests, the mRNA-based AHPV test shows a similar sensitivity and a higher specificity in high-grade cervical lesion detection 25. Our results showed that the prevalence of HSIL+lesions in women with ASC-US/hrHPV+ based on the Aptima assay are low (12.2%), which is similar to the findings of previous studies (<10%) 17 20 26. However, Jiang et al showed that the prevalence of HSIL+lesions in women with ASC-US/hrHPV+ based on the hrHPV genotype was 19.5% 27.…”
Section: Discussionsupporting
confidence: 87%
“…Due to these uncertainties, the management of ASC-US/hrHPV-positive patients has been challenged since the 2003 approval of cytology and HPV co-testing by the US Food Drug Administration. Particularly for Aptima assay, there were limited studies with respect to cervical pathology among ASC-US/hrHPV+women in China even decades after its implemention as an adjunct in cervical cancer screening 17. The aim of this study was to evaluate the immediate histological correlation in women with ASC-US/hrHPV+detected by Aptima assays in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…A study in New York of 2145 women with ASC-US who tested positive for the Aptima HPV mRNA test and underwent colposcopic directed biopsy found that the proportion of CIN 2 + was 8.8%. When considering age groups, the highest incidence of CIN 2 + was found in those younger than 25 years compared to the age group 50–59 years, with rated of 15.4% versus 4.8%, respectively 29 . The highest detection proportion of HSIL + was in those aged ≤ 30 years (40.5%) and the lowest in the age group 51–60 years (21.7%).…”
Section: Discussionmentioning
confidence: 95%
“…They compared Aptima and Cobas platforms, and the PPV was higher for Aptima regarding ≥HSIL lesions (Aptima 20.3%, Cobas 18.8%). In 2021, Wang et al [15] performed a retrospective study with Aptima on a large group of patients with ASCUS cytology. The PPV of the Aptima platform for ≥HSIL lesions was 8.8%.…”
Section: Discussionmentioning
confidence: 99%